ANALISIS DAMPAK PERTUMBUHAN EKONOMI, KESENJANGAN ANTAR DAERAH DAN TENAGA KERJA TERSERAP TERHADAP KESEJAHTERAAN DI KABUPATEN/KOTA PROVINSI JAWA TENGAH DALAM ERA DESENTRALISASI FISKAL - Hadi Sasana (Jurnal Bisnis dan Ekonomi, 2009)
In the autonomy and fiscal decentralization era, local governments is providedwith authority to increase their income and to conduct allocative function in settingpriority of local development. This research is intended to examine the influence ofeconomic growth, inter-regional inequality, employment, on welfare atregencies/municipalities level in Central Java Province.Research population consist of 29 regencies and 6 municipalities, employingsecondary data from Central Bureau of Statistic of Central Java Province andregencies/municipalities level in Central Java Province within the period of 2001 upto 2005. Data analysis is conducted by using path analysis .The results of this study indicate that, first, economic growth has a positiveand significant effect on welfare at regencies/municipalities level in Central JavaProvince. Second, inter-regional inequality has a negative and significant effect onwelfare at regencies/municipalities level in Central Java Province. Third,employment rate has a negative and significant effect on welfare atregencies/municipalities level in Central Java Province.Key words:, economic growth, inter-regional inequality, employment, welfare